The Efficacy of Medium-Chain Triglyceride on the Prognosis and Outcome of Suspected COVID-19 Outpatients: A Randomized Controlled Trial - Mohammad Setayesh; Alireza Zahedi-Neyestani; Golamreza Asadikaram; Haleh Tajadini; Masoud Moghadari; Armita Shahesmaeili; Saeideh Jafarinejad-Farsangi; Fatemeh Sadat Hasheminasab; Ehsan Amiri-Ardekani (Journal of Kerman University of Medical Sciences, 2023)
Background: The novel coronavirus disease (COVID-19), as a global concern, has affected different economic and social aspects, as well as health costs in various communities. Finding effective and available treatment is an urgent need. A recent study has demonstrated that the ketogenic diet (KD) activates innate immunity and has a protective property against virus infection. Accordingly, we conducted this study to find the effect of oral medium-chain triglyceride (MCT) on COVID-19 and its clinical manifestations. Methods: This was a randomized clinical trial on 195 patients clinically suspected of COVID-19 referred to infectious disease clinics of Kerman. Patients were randomly assigned into two groups. The Control group received standard supportive treatment, the recommendation for carbohydrate avoiding and diet modification. Patients in the intervention group received all mentioned recommendations beside MCT oil. Patients` clinical symptoms, including body temperature, respiratory rate, body pain, and dyspnea, were recorded in a checklist and analyzed. Results: The mean age of patients was 37.78 ± 12.42 years in the intervention group and 40.81 ± 13.23 years in controls (P = 0.231). The patients in the intervention group had lower duration of weakness (P = 0.004), body pain (P = 0.004), dyspnea (P = 0.004), gastrointestinal manifestations (P<0.001), sore throat (P<0.001), increased respiratory rate (P<0.001), and high intensity of cough (P=0.002). Indeed, weakness, cough frequency, sore throat, and gastrointestinal complications were significantly lower in the females of the intervention group (P=0.006, P=0.030, P=0.005, and P=0.001, respectively). In contrast, in the males of the intervention group, manifestations such as respiratory rates, dyspnea, cough intensity, and sore throat were significantly lower than those in the control group. Conclusion: Administration of MCT in outpatients suspected of COVID-19 alleviated clinical symptoms such as increased respiratory rate, cough intensity, dyspnea, body pain, and gastrointestinal symptoms and helps them overcome the probable disease morbidity.